Comprehensive Air Quality Index Assessment Incorporating NO2, PM2.5, PM10, and O3 in Ondo State, Nigeria - Akinyinka Akinnusotu; Francis Olawale Abulude; Ebenezer Alaba Adeoya; Oluwole Olumide Adeyemi; Sikirat Bidemi Jiddah-Kazeem; Kikelomo Mabinuola Arifalo; Emmanuel Awogbindin; Acha Sunday (Jurnal Pendidikan Geografi Gea, 2023)
This study conducted in Ondo State, Nigeria, employs an Air Quality Index (AQI) to evaluate the air quality in nine communities, focusing on pollutants like ozone (O3), nitrogen dioxide (NO2), fine particulate matter (PM2.5), and coarse particulate matter (PM10). The study stands out due to its comprehensive examination of various pollutants and their combined impact on air quality. Satellite data from IQAir's AirVisual website was utilized to track pollution levels across these areas over six months. This data was then used to establish daily AQI values, offering a unified measure to assess air quality and related health risk. The AQI provides a holistic understanding of air quality in Ondo State, aiding in better evaluation of circumstances and potential health consequences. The research highlighted considerable air quality discrepancies across different locations, identifying PM2.5 and NO2 contributors poor air quality. These findings serve a reference for future monitoring and  formulation